Effects of Calcium on Sugar Transport in Azotobacter vinelandii - Wong, T. Y. (1993)
A fast and environmentally safe procedure was used to study sugar uptake by Azotobacter vinelandii. Transport experiments were performed in a 24-well plate and aerated by rapid oscillatory vibration. Samples were washed by centrifugation and dissolved in biodegradable scintillation cocktail for counting. At cell concentrations up to 6 × 10(8) cells per ml, the uptake of sucrose was a function of time and was proportional to the cell concentration. This modified uptake assay was used to test the effect of cations on sugar uptake in A. vinelandii. Results showed that Ca(2+) at 1 to 2 mM stimulated sucrose uptake by decreasing the apparent K(m) of sucrose transport. Higher Ca(2+) concentrations inhibited sucrose uptake in this organism.